Tweets don’t vote – Twitter discourse from Wales and England during Brexit - Peixoto Gomes, Larissa (Frontiers in Sociology, 2023)
The Welsh vote for 'leave' in the Brexit referendum surprised some academics and analysts due to its strong preference for Labour and its close financial ties to the EU. It also brought up a debate about apparent differences in Welsh and English attitudes towards race, ethnicity, and migration, with the former often claiming to have a more positive stance regarding the presence of ethnic minorities and foreign nationalities. This paper proposes to analyse discourse posted on Twitter during June 2016, specifically targeting Wales and England with the aim to offer insight into the perceptions and beliefs of Welsh and English individuals on the platform and if attitudes on race, ethnicity, and migration played a significant role. Counterfactuals are checked with posts from the first few weeks of the refugee crisis in Afghanistan in 2021, the war on Ukraine, and the announcement of the Rwanda policy.The current discussion of Welsh national identity includes its claims as a 'nation of sanctuary' and that understands oppression and marginalisation. Thus, Welsh perspectives on Brexit become an interesting viewpoint to comprehending ethnic minorities and foreigners as it creates a possible conflict between the institutional discourse, cultural views, and perceived economic needs. In this context, this paper takes the view that Twitter is an area where individuals post their thoughts uninhibited, and where we can conduct an aggregate analysis of that public sentiment. This is a provisional file, not the final typeset article as a Labour stronghold due to its electing a majority of Labour MPs for the House of Commons and its local authorities and maintaining a Labour government since devolution. This has led to views and policies that claim Wales to be more progressive and welcoming to ethnic minorities and foreigners in comparison to its neighbour. Although Twitter data is not statistically representative of any population, it is exemplary of how conversations flow during major events. Studying the content of tweets has become a staple in public opinion research, aiding in analyses of information flow, fake news dispersion, and political opinion building (